The effect of talent management strategies on quality of services in improving citizens’ satisfaction: a study in the federal authority for identity and citizenship in Emirate of Abu Dhabi - Alsereidi, Saeed Mohamed Howaishel Ghareib (2023)
The main objective of this research is to study talent management strategies to improve the quality of services in order to satisfy citizens with the services provided by the Federal Authority for Identity and Citizenship in the Emirate of Abu Dhabi. This was done by testing the impact of the strategy of attraction, talent development, talent retention, and talent succession planning as independent variables on citizen satisfaction as a dependent variable and the impact of service quality as an intermediary variable between talent management strategies on the one hand and citizen satisfaction with the services provided on the other hand. The research study is a quantitative research study that made use of statistical evaluation based on detailed solutions and techniques of variance and covariance, correlation, and regression. The study is huge research in the feature bearing in mind that it deals with a site of study that is talent management strategies to improve the quality of services for citizens’ satisfaction with the services provided by the Federal Authority for Identity and Citizenship in the Emirate of Abu Dhabi, where there have already been previous studies conducted. Regarding the role of talent management strategies to improve the quality of services for citizen satisfaction, a questionnaire was created from the literary works and modified to match the study conditions. The population of this assessment are the employees of the Federal Authority for Identity and Citizenship in the Emirate of Abu Dhabi, the target sample size is 332 but the actual valid data set has 301 samples. The results of the main dependent variable, citizens’ satisfaction with the services provided by the authority, show satisfactory predictive power and great predictive importance. The proposed model can explain 76.2% of the variance in the degrees of spelling in citizens’ satisfaction with the services provided by the Federal Authority for Identity and Citizenship in the Emirate of Abu Dhabi, which has a great relationship with talent management strategies. The results of the analysis of the mediating role of service quality were satisfactory results in the relationship between talent management strategies and citizen satisfaction.